Methods and Models for Metabolic Assessment in Mice. (21st May 2013) - Pacini, G.; Omar, B.; Ahrén, B.
Abstract : The development of new therapies for the treatment of type 2 diabetes requires robust, reproducible and well validated in vivo experimental systems. Mice provide the most ideal animal model for studies of potential therapies. Unlike larger animals, mice have a short gestational period, are genetically similar, often give birth to many offspring at once and can be housed as multiple groups in a single cage. The mouse model has been extensively metabolically characterized using different tests. This report summarizes how these tests can be executed and how arising data are analyzed to confidently determine changes in insulin resistance and insulin secretion with high reproducibility. The main tests for metabolic assessment in the mouse reviewed here are the glucose clamp, the intravenous and the oral glucose tolerance tests. For all these experiments, including some commonly adopted variants, we describe: (i) their performance; (ii) their advantages and limitations; (iii) the empirical formulas and mathematical models implemented for the analysis of the data arising from the experimental procedures to obtain reliable measurements of peripheral insulin sensitivity and beta cell function. Finally, a list of previous applications of these methods and analytical techniques is provided to better comprehend their use and the evidences that these studies yielded.